The Effectiveness of Application of Lectures and Audiovisual Methods on Increasing Conscious Behavior in Cancer Early Detection Efforts Breasts of Housewives in Alue on District Kaway XVI - Annisa, Suci; Husna, Arfah (Universitas Teuku Umar, 2022)
Breast cancer is the type of cancer that causes the biggest cause of death among women as well as the highest number of cases in the world. The number of breast cancer patients in West Aceh in 2017 was 22 people, then decreased to 10 people in 2018, and increased from 10 people to 17 people in 2019. Breast cancer cases increased due to lack of knowledge about BSE behavior, early symptoms caused by breast cancer and breast cancer risk factors. One way to prevent breast cancer is easy, inexpensive, and can be done yourself at home is to use the BSE (Breast Self-Examination) method. The purpose of this study was to determine the effectiveness of the application of the lecture and audiovisual methods before and after the intervention was given regarding the early detection of breast cancer in housewives in Alue on Village, Kaway XVI District. This type of research is a quasi-experimental with a two-group pre-test-post-test approach. The sample is 24 respondents with purposive sampling technique. The analysis used is univariate and bivariate. The results of the Wilcoxon test showed an increase in BSE behavior (p = 0.002) in housewives in Alue On village. The results of the t test show that the t-count value is 2.980 > ttable 2.074, meaning that there is a difference in the average results of BSE behavior using the lecture and audiovisual methods where the group using the audiovisual method is more effective at increasing BSE behavior in early detection of breast cancer in housewives. Alue On village, Kaway XVI sub-district. It is recommended to mothers who have a good understanding of early detection of breast cancer to provide information to mothers whose understanding is still lacking.